Bioinformatic analysis and experimental validation identified DNA methylation–Related biomarkers and immune-cell infiltration of atherosclerosis - Xu, Congjian; Sun, Di; Wei, Changmin; Chang, Hao (Frontiers in Genetics, 2022)
Background: DNA methylation is an important form of epigenetic regulation and is closely related to atherosclerosis (AS). The purpose of this study was to identify DNA methylation-related biomarkers and explore the immune-infiltrate characteristics of AS based on methylation data. Methods: DNA methylation data of fifteen atherosclerotic and paired healthy tissues were obtained from gene expression omnibus database. Differential methylation positions (DMPs) and differential methylation regions (DMRs) were screened by the ChAMP R package. The methylation levels of DMPs located on CpG islands of gene promoter regions were averaged. The limma R package was used to screen differentially methylated genes in the CpG islands of the promoter regions. The diagnostic values of the methylation levels were evaluated using the pROC R package. The EpiDISH algorithm was applied to quantify the infiltration levels of seven types of immune cells. Subsequently, three pairs of clinical specimens of coronary atherosclerosis with Stary's pathological stage III were collected and the methylation levels were detected by the methylation-specific PCR (MS-PCR) assay. Western blot was performed to detect the protein expression levels of monocyte markers. Results: A total of 110, 695 DMPs and 918 DMRs were screened in the whole genome. Six genes with significant methylation differences in the CpG islands of the promoter regions were identified, including 49 DMPs. Three genes (GRIK2, HOXA2, HOXA3) had delta beta greater than 0.2. The infiltration level of monocytes was significantly up-regulated in AS tissues. MS-PCR assay confirmed the methylation status of the above three genes in AS samples. Western blot results showed that the expression levels of monocyte marker CD14 and M1-type macrophage marker CD86 were significantly increased in AS, while M2-type macrophage marker protein CD206 was significantly decreased. Conclusions: This study identified potential DNA methylation-related biomarkers and revealed the role of monocytes in early AS.